2003
DOI: 10.1021/ja038405h
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium Ion-Terminated Self-Assembled Monolayers on Au:  Effects of Counteranions on Surface Wettability

Abstract: Self-assembled monolayers presenting imidazolium ions at the tail ends (SAMIMs) having different counteranions have been prepared on Au, and the measurement of water contact angles of the surfaces proved to be an extremely valuable simple technique for quantifying the effects of counteranions on hydrophilicity and hydrophobicity of SAMIMs, which will be extrapolated to the water miscibility of the related ionic liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(135 citation statements)
references
References 31 publications
11
124
0
Order By: Relevance
“…From Figure 2a, the size of CNT aggregates is about 30-50 µm, however there is no obvious CNT aggregates in Figure 2b. The imidazolium-functionalized CNTs bearing hydrophilic Chlorine anion were found to convert the hydrophobic surface of CNT to hydrophilic 40,41 . After screening various solvent systems, a mixture of ethanol and acetone (3:1, v/v) was found to favor the uniform dispersion of the CNTs-IL.…”
Section: Resultsmentioning
confidence: 99%
“…From Figure 2a, the size of CNT aggregates is about 30-50 µm, however there is no obvious CNT aggregates in Figure 2b. The imidazolium-functionalized CNTs bearing hydrophilic Chlorine anion were found to convert the hydrophobic surface of CNT to hydrophilic 40,41 . After screening various solvent systems, a mixture of ethanol and acetone (3:1, v/v) was found to favor the uniform dispersion of the CNTs-IL.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the extremely low vapor pressures and the interesting transport as well as electrochemical properties of this material class, ILs were used as reaction media, [1,2] as electrolytes in batteries and supercapacitors, [3][4][5][6][7] in solar and fuel cells, [8][9][10][11][12][13] for electrochemical deposition of metals and semiconductors, [14] as additives for stabilizing proteins, [15] for liquid-liquid extractions [16] and in nanoscience. [17][18][19] The fundamental physical properties (e.g. melting point, viscosity, conductivity, density etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Choi et al prepared self-assembled monolayers (SAM) with imidazolium groups on smooth Au and Si/SiO 2 substrates [1][2][3]. They studied the effect of a series of anions as shown in Figure 1 and In order to elaborate reversible superhydrophobic properties by ion exchange, gold micro and nanostructured substrates were performed by electroless etching process by immersing silicon substrates in aqueous solution of HAuCl 4 and HF (Figure 2).…”
Section: Ion Exchangementioning
confidence: 99%
“…In 2004, Choi et al prepared self-assembled monolayers (SAM) with imidazolium groups on smooth Au and Si/SiO 2 substrates [1][2][3]. They studied the effect of a series of anions as shown in Figure 1 and they found that the surface hydrophobicity increases like this: Br The substituent has also an important influence on the surface wettability [3,4].…”
Section: Ion Exchangementioning
confidence: 99%